The Mammalian Auditory Pathways Synaptic Organization and Microcircuits (Springer Handbook of Auditory Research,, 2018)
This volume presents an overview of the functional anatomy of the central auditory system integrated with cell biology, synaptic physiology, and electrophysiology. • Introduction to Mammalian Auditory Pathways Douglas L. Oliver and Nell B. Cant • Overview of Auditory Projection Pathways and Intrinsic Microcircuits Nell B. Cant and Douglas L. Oliver • Microcircuits of the Ventral Cochlear Nucleus Maria E. Rubio • Microcircuits of the Dorsal Cochlear Nucleus Laurence O. Trussell and Donata Oertel • Integration of Synaptic and Intrinsic Conductances Shapes Microcircuits in the Superior Olivary Complex Conny Kopp-Scheinpflug and Ian D. Forsythe • Neurons, Connections, and Microcircuits of the Inferior Colliculus Tetsufumi Ito and Manuel S. Malmierca • Sensing Sound Through Thalamocortical Afferent Architecture and Cortical Microcircuits Heather L. Read and Alex D. Reyes • Auditory Cortex Circuits Eike Budinger and Patrick Kanold • Circuits for Modulation of Auditory Function Brett R. Schofield and Laura Hurley Douglas S. Oliver is Professor in the Department of Neuroscience, UConn Health, University of Connecticut, Farmington Nell B. Cant is Professor in the Department of Neurobiology, Duke University Medical Center, Durham Richard R. Fay is Distinguished Research Professor of Psychology at Loyola University Chicago Arthur N. Popper is Professor Emeritus and research Professor in the Department of Biology at the University of Maryland, College Park.